Endoscopic and Percutaneous Biliary Interventions after Liver Transplantation: Nationwide Data in Korea - Seung Bae Yoon; Jungmee Kim; Chang Nyol Paik; Dong Kee Jang; Jun Kyu Lee; Won Jae Yoon; Jung-Wook Kim; Tae Hee Lee; Jae-Young Jang (Gut and Liver, 2022)
Background/Aims: Biliary complications including biliary strictures and bile leaks are the most common complications that occur after liver transplantation (LT). Endoscopic treatment with endoscopic retrograde cholangiography (ERC) is considered the first-line treatment, and percutaneous transhepatic cholangiography (PTC) can serve as an alternative or rescue therapy. However, nationwide clinical data on the frequency of ERC and PTC following LT have not yet been investigated. Methods: Using the nationwide claims database, we investigated patients who underwent LT between 2012 and 2014 in Korea and followed them until 2015. We analyzed the prevalence and characteristics of patients and biliary procedures, including ERC and PTC implemented after LT. Results: A total of 3,481 patients underwent LT during the 3-year study period. Among them, 3.0% of patients underwent biliary intervention postoperatively during the same hospitalization period, and 21.4% of patients received biliary intervention later on after initially being discharged from the hospital following LT. A total of 16.9% and 12.1% of patients underwent ERC and PTC after LT, respectively. The median period from LT to the first biliary intervention was 7.8 months (interquartile range, 3.5 to 14.6 months), and these patients underwent an average of 3.2±2.8 biliary procedures during the follow-up period. Patients undergoing living donor LT were more than twice as likely to undergo biliary procedures as those undergoing deceased donor LT (25.5% vs 12.1%). Conclusions: Approximately one-fourth of patients in Korea who underwent LT subsequently underwent ERC or PTC. Compared with deceased donor LT patients, those undergoing living donor LT underwent more biliary interventions and were more difficult to treat.